Stability of forming induced residual stresses in stainless steel components under mechanical load - Jobst, Andreas; Merklein, Marion (Manufacturing Letters, 2023)
Cold forward extrusion leads to the generation of residual stresses, which can have an advantageous or detrimental effect on the operating behavior of the formed components. In industrial practice, energy-intensive annealing steps are often used to remove unknown stress states and thus prevent unexpected failures. Residual stress-related knowledge can therefore help to save energy and resources. To be able to estimate the effects, not only sign and magnitude need to be known, but also the residual stress stability under typical operating loads. In this paper, stainless steel X6Cr17 (DIN 1.4016, AISI 430) is formed by forward rod extrusion at room temperature. The forming process leads to residual stresses in the formed components, which are subsequently subjected to mechanical testing. To represent different initial states, components with varied die opening angles are produced and tested. A modified 3-point bending setup is used to generate a defined tensile load stress in the part surface. The results show a behavior of the residual stresses, which is depending on the load magnitude, the initial stress state and the work hardening distribution in the part. While the number of cycles has an influence, the largest changes occur in the first stroke.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Extrusion; Residual stress; Stability; Stainless steel